Does 3-dimensional facial attractiveness relate to golden ratio, neoclassical canons, ‘ideal’ ratios and ‘ideal’ angles? - Roger A. Zwahlen; Alexander T. H. Tang; Wai Keung Leung; Su Keng Tan (Maxillofacial Plastic and Reconstructive Surgery, 2022)
Abstract Background The established recommendations and guidelines regarding ideal measurements for an attractive face are mostly based on data gathered among Caucasian population. The aim of this study was to examine the relationship between perception of 3-dimensional facial attractiveness and golden ratio, neoclassical canons, ‘ideal’ ratios and ‘ideal’ angles in Hong Kong Chinese. Methods Thirty 3-D photographs (15 males and 15 females) were shown to 101 laypersons and 60 patients seeking orthognathic treatment. The photographs were rated based on a 100 mm visual analogue scale (VAS) from 0 (very unattractive) to 100 (very attractive). Results More than half of the measurements (42/77) in females and thirty-two measurements in males were found to be significantly different from the ideal target value (p < 0.05) upon the comparison of the attractive faces with golden ratio, neoclassical canons, ‘ideal’ ratios and ‘ideal’ angles. Meanwhile, correlation tests between VAS scores and the parameters detected significant results (p < 0.05) in only six ratios, eight angles, one neoclassical canon and one proportion. Conclusions Despite several renowned ‘ideal’ parameters of attractive faces that have been recommended in the literature, only a few of them were found to be significantly correlated with attractive faces in Hong Kong Chinese.